2022
DOI: 10.1021/acs.inorgchem.2c02800
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Salts of Sensitive N,N′-(3,5-Dinitropyrazine-2,6-diyl)dinitramide Stabilized through Three-Dimensional Intermolecular Interactions

Abstract: N-nitration of 2,6-diamino-3,5-dinitropyrazine (ANPZ) leads to a sensitive energetic compound N,N′-(3,5dinitropyrazine-2,6-diyl)dinitramide. This nitro(nitroamino) compound was stabilized by synthesizing energetic salts, dipotassium (3,5-dinitropyrazine-2,6-diyl)bis(nitroamide) (3) and diammonium (3,5-dinitropyrazine-2,6-diyl)bis(nitroamide) (4). Compounds 3 and 4 are fully characterized by single-crystal X-ray diffraction. Compound 3 exhibits a three-dimensional energetic metal−organic framework (3D EMOF) str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The DSC curve shows a small endothermic peak at 193 °C before decomposition. As can be seen in Figure S6, it shows a very sharp onset decomposition temperature at 291 °C with 5 °C min À 1 heating rate, which is better than the previously reported potassium EMOFs K 2 DNPDP [28] (220 °C), K 2 DNAF [24] (288 °C) and close to K 2 DNADFP [18] (292 °C), K 2 NPA [27] (315 °C), and also higher or close to the present commonly used heat-resistant explosive HMX (279 °C) and HNS (318 °C). The TGA curve exhibits two distinct weight loss peaks under a heating rate of 5 °C min À 1 .…”
Section: Thermal Studiesmentioning
confidence: 52%
See 1 more Smart Citation
“…The DSC curve shows a small endothermic peak at 193 °C before decomposition. As can be seen in Figure S6, it shows a very sharp onset decomposition temperature at 291 °C with 5 °C min À 1 heating rate, which is better than the previously reported potassium EMOFs K 2 DNPDP [28] (220 °C), K 2 DNAF [24] (288 °C) and close to K 2 DNADFP [18] (292 °C), K 2 NPA [27] (315 °C), and also higher or close to the present commonly used heat-resistant explosive HMX (279 °C) and HNS (318 °C). The TGA curve exhibits two distinct weight loss peaks under a heating rate of 5 °C min À 1 .…”
Section: Thermal Studiesmentioning
confidence: 52%
“…Recently, Shreeve and coworkers reported the potassium EMOF based on six‐membered N,N′‐(3,5‐dinitropyrazine‐2,6‐diyl)dinitramide, which possesses high sensitivity and lower thermal decomposition temperature owing to the presence of two nitro and nitramino groups in the ligand (Scheme 1). [28] Among six‐membered heterocycles, pyrimidines and pyrazines exhibit great potential in the field of energetic materials due to their versatile, modifiable positions for incorporating different explosophoric groups. Numerous studies have shown that these compounds possess excellent thermal stability and maintain low sensitivity to external factors [21,29,30] .…”
Section: Introductionmentioning
confidence: 99%
“…Heterocyclic backbones, such as the five-and sixmembered rings (pyrazole, imidazole, triazole, tetrazole, oxadiazole, pyrazine, triazine, pyrimidine, pyridazine, and tetrazine), are commonly regarded as the primary building blocks of modern high energy density materials (HEDMs) [11,[14][15][16][17][18]. The incorporation of various explosophoric groups such as nitro (-NO 2 ), nitramine (-NHNO 2 ), azide (-N 3 ), etc., on a particular heterocyclic framework is a widely used and effective strategy to boost the detonation performance of the compounds [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the coordination ability of the potassium ions, energetic coordination compounds (ECCs) formed by potassium−oxygen cooperation have attracted special attention owing to their unique structures, good energetic properties, and acceptable densities (∼2.0 g cm −3 ). 22 density (ρ < 2.0 g cm −3 ), and inferior oxygen balance (negative).…”
mentioning
confidence: 99%
“…Notable examples include DTAT-K, K 2 DNABT, potassium 4,5-bis­(dinitromethyl)­furoxanate, and K 2 BDFOF (Figure b). Due to the coordination ability of the potassium ions, energetic coordination compounds (ECCs) formed by potassium–oxygen cooperation have attracted special attention owing to their unique structures, good energetic properties, and acceptable densities (∼2.0 g cm –3 ) . However, in comparison with LA ( T dec = 315 °C; d = 4.80 g/cm 3 ), most of the potassium-based initiators have poor thermal stability ( T dec < 200 °C), lower density (ρ < 2.0 g cm –3 ), and inferior oxygen balance (negative).…”
mentioning
confidence: 99%